Kesiapan Digitalisasi Layanan Sistem Pemerintahan Berbasis Elektronik Pada Badan Pengkajian dan Penerapan Teknologi (BPPT) - Pinggar Hawa; Roy Valiant Salomo (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
E-Government in Indonesia is not something new, because the Indonesian government has standarized e-Government in terms of Electronic-Based Government Systems which aims to improve the quality of public services effectively and efficiently. This research is expected to present the readiness analysis of the Agency for the Assessment and Application of Technology (BPPT) in implementing significant changes which are the implementation of Electronic-Based Government Systems with the presence of 41 applications to digitizing administrative services, and the efforts made to perform a proper digital transformation. To achievieving a proper result, the author utilize the post-positivism method with a descriptive analysis approach which obtained through in-depth interviews of the four dimensions of Readiness to organizational change that consist of Change Specific efficacy, Appropriateness, Management support, and Personal Valence. These dimensions will provides information regarding the readiness conditions of Agency for the Assessment and Application of Technology to implement the Digitalization of e-office which are ready but not in ideal condition because the planned Electronic-Based Government System is still not fully integrated, implemented and tested which requires further development.